An unusual Northwest–Southeast oriented Meiyu rain belt in 2021 - Huo, Liwei; Guan, Zhaoyong; Zhang, Mengke; Jin, Dachao; Wang, Ji; Shi, Yinglong; Wang, Yi; Liu, Yin; Liu, Chun (Frontiers in Earth Science, 2023)
Affected by the East Asian summer monsoon, summer floods occur frequently in eastern China, causing huge economic losses and social impacts. In 2021, the precipitation anomaly during the Meiyu period in Yangtze-Huaihe River Valley (YHRV) was abnormally high, with a value of 188.0 mm, about 1.7 standard deviations above normal. However, it did not cause serious flood disasters. This was mainly due to the existence of two precipitation anomaly centers in YHRV, which shared the impact of the excessive precipitation. These two centers were located at the junction of Anhui Province and Henan Province and the junction of Jiangsu Province, Anhui Province and Jiangxi Province, respectively. And more notably, the 2021 Meiyu precipitation anomalies were distributed in a Northwest-Southeast oriented band that is very rare. During the 2021 Meiyu period, the western Pacific subtropical high (WPSH) weakened and extended westward. An anticyclonic circulation anomaly in the lower troposphere was observed over eastern China, which was found to be related to the quasi-stationary wave trains propagating eastward from Hainan Island to the northwestern Pacific by vorticity budget analysis. And the Rossby wave source term played a critical role. In addition, the tropical Atlantic anomalous warming produced convergence anomaly over the eastern Mediterranean and excited quasi-stationary wave trains propagating downstream at the mid-latitudes in upper layers through a monsoon-desert-like teleconnection. It raised the geopotential height over eastern China and thus favored the westward extension of WPSH. These large-scale circulation anomalies generated the anomalous easterly winds along the eastern coast of China and the anomalous southwesterly winds from Guangxi Province to the middle and lower reaches of the Yangtze River. Similar features can be found in the anomalous water vapor transport and the water vapor converged in the YHRV. The above-mentioned reasons jointly caused the abnormally high precipitation anomaly and its unusual pattern in the 2021 Meiyu season. This study might provide a scientific basis and clues for understanding Meiyu precipitation anomalies and disaster prevention and mitigation.